Hydatid cyst of femur, radiologically mimicking a sarcoma. Issue 10 (20th August 2019) - Ramteke, Prashant; Phulware, Ravi H.; Shende, Tripti; Sahoo, Biswajit; Barwad, Adarsh
Abstract: Hydatid disease is a rare pathology, but relatively common in the Mediterranean, the Middle East, Central Asia, and East Africa. It may develop in almost any part of the body, although most hydatid cysts occur in the liver or in the lung. Bone involvement is rare, and accounts for only 0.5% to 4% of all locations. Most of the hydatid cyst are diagnosed on the basis of their clinical and radiological presentation. However, in cases with an atypical presentation, FNAC may be used to evaluate the nature of lesion.